Analisis Pengaruh CAR, NPF, Dan BOPO Terhadap Return On Asset Pada PT BTPN Syariah Tbk. Periode 2018-2022 - Fitri Indriyati; Putri Apria Ningsih; Lidya Anggraeni (Politeknik Kampar, 2023)
This research is based on the movement of Return on Assets (ROA) at PT BTPN Syariah Tbk. which experienced a variable movement between 2018 and 2022. The purpose of this study was to determine the effect of the ratios of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Operating Expenses and Operating Income (BOPO) which are independent variables in this study. Return on Assets (ROA) which is the dependent variable at PT BTPN Syariah Tbk. The research method used is a quantitative technique using a purposive sampling technique. The type of data used is basic data using the documentary data collection method resulting from the use of quarterly financial report data published on the official website of PT BTPN Syariah Tbk. The results of this study indicate that CAR, NPF, simultaneously have no significant effect on Return On Assets (ROA), while BOPO has a significant effect on Return On Assets (ROA), with a significance of 0.164 < ? 0.05 and a calculated t value of -1.458 which shows a negative direction, then NPF has a significance value of 0.681 > ? 0.05 and a calculated t value of -0.419 which indicates a negative direction and BOPO has a significant negative effect on ROA with a significance value of 0.000 BOPO < ? 0.05 and a calculated t value of -0.544 indicates a negative direction. Based on the results of the coefficient of determination test, it shows that as much as 67% of the variation in ROA which can be explained by variations of the three independent or independent variables, namely CAR, NPF and BOPO simultaneously, 33% is explained by other causes outside the model which are the contributions of other independent variables outside three variables.